Pengaruh Self Efficacy, Kompetensi dan Dukungan Organisasi Terhadap Kinerja Karyawan Pada PT Indo Bismar Surabaya - Ratna Putri Wulandari; Siti Mujanah (Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
The research objectives to be achieved in accordance with the formulation of the problem above are to determine, analyze and answer the effect of Self Efficacy, Competence and Organizational Support on Employee Performance of PT Indo Bismar Surabaya. This research uses quantitative methods. Sampling was carried out by saturated sampling technique with a questionnaire method with 51 employees and analyzed using the Statistical Package for the Social Sciences (SPSS) version 25. The data analysis technique used is multiple linear regression analysis. Meanwhile, the classical assumption tests used include Normality Test, Multicollinearity Test, Autocorrelation Test, and Heteroscedasticity Test. The results showed in the t test conducted partially that the Self Efficacy variable had a significant positive effect on employee performance, the Competency variable had a significant positive effect on employee performance and the Organizational Support variable had a significant positive effect on employee performance. Regarding the f test, it shows that the variables of Self Efficacy, Competence and Organizational Support simultaneously affect the performance of employees of PT Indo Bismar Surabaya.